Prototypical dimensions of business opportunity in early stages of the entrepreneurial process - Costa, S. (2014)
The purpose of this paper is to describe how individuals with no entrepreneurial experience use prototypical dimensions of business opportunities at the first two stages of the entrepreneurial process: recognition and decision to launch a venture. Previous studies have described the business opportunity prototype (Baron & Ensley, 2006); however, they do not describe how it is used and rely on retrospective data and entrepreneurs' prior experience. We intend to overcome these gaps by using two hypothetical scenarios and three conditions, creating a first entrepreneurial experience for individuals, having thus a 2 (scenario A and B) X 3 (condition: "Problem solving", "Cash flow", "Manageable risk") design plan with a total of six groups. Our results allow us to describe how individuals use the prototype in the first two stages of the entrepreneurial process. Specifically, we have a better understanding of the importance of risk, customers, and profit in both stages. Both in the recognition and the decision stages, risk is the most important factor, but profit and customers are considered differently in the two stages. In recognition, profit is more important than customers; however, in the decision stage, customers are a major concern for the participants. These results provide relevant information on the first entrepreneurial experience of individuals, which is crucial given the recognized need to promote entrepreneurial initiatives and behavior.